Development and validation of hospital information system-generated indicators of the appropriateness of oral anticoagulant prescriptions in hospitalised adults: the PACHA study protocol. Issue 8 (31st August 2017) - Petit-Monéger, Aurélie; Thiessard, Frantz; Jouhet, Vianney; Noize, Pernelle; Berdaï, Driss; Kret, Marion; Sitta, Rémi; Salmi, Louis-Rachid; Saillour-Glénisson, Florence
Abstract : Introduction: The appropriateness of oral anticoagulant prescriptions is a major challenge to improve quality and safety of care. As indicators of the appropriateness of oral anticoagulant prescriptions are lacking, the aim of the study is to develop and validate a panel of such indicators, in hospitalised adults, from the hospital information system of two university hospitals in France. Methods and analysis: The study will be carried out in four steps: (1) a literature review to identify indicators of the appropriateness of oral anticoagulant prescriptions and their conditions of appropriateness; (2) a Delphi consensus method to assess the potential utility and operational implementation of the selected indicators; (3) techniques of medical data search to implement indicators from the hospital information system and; (4) a cross-sectional study to assess the ability of indicators to detect inappropriate oral anticoagulant prescriptions, performance of medical data search techniques for tracking or retrieving information and the ability of tools to be transferred into other institutions. The fourth step will include up to 80 patient hospital stays for each indicator, depending on the prevalence of inappropriate prescriptions estimated in interim analyses. Ethics and dissemination: This work addresses the current lack of quality indicators of the appropriateness of oral anticoagulant prescriptions. We aim to develop and validate such indicators for integrating them into hospital clinical practice, as part of a structured approach to improve quality and safety of care. As each hospital information system is different, we will propose tools transferable to other healthcare institutions to allow an automated construction of these indicators. The PACHA study protocol was approved by institutional review boards and ethics committees (CPP Sud-Ouest et Outre Mer III—DC 2016/119; CPP Ile-de-France II—CDW_2016_0014). Registration details: Clinical Trial.gov registration: NCT02898090 .